PENGARUH FIRM SIZE, WINNER/LOSER STOCK, DAN DEBT TO EQUITY RATIO TERHADAP PERATAAN LABA (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Muhammad Arfan; Desry Wahyuni (Program Magister Akuntansi Unsyiah, 2010)
Income smoothing can be defined as a means used by management to diminish the variability of a stream of reported income numbers relative to some perceived target stream by the manipulation of artificial (accounting) and real (transactional) variables. To achieve certain purposes, the management thinks that income smoothing is a common action to be done. This action can be taken for the importances of investors, creditors, even for the management’s importances. The objective of this research is to examine and analyze the influance of firm size, winner/loser stock, and debt to equity ratio toward income smoothing on listed manufacturing companies at the Indonesian Stock Exchange. The research type used in this research is verificative or hypothesis testing research. By using census method and balanced panel data, there are 105 firm observations fulfilling the population criteria during 3 years since 2005 until 2007. The data type used are secondary data obtained from the capital market reference center at the Indonesian Stock Excange.The logistic regression analysis model is used to test the hypothesis. The results of this research show that: 1) Simultaneously, firm size, winner/loser stock, and debt to equity ratio have influence toward income smoothing on listed manufacturing companies at the Indonesian Stock Exchange, 2) Firm size has positive influance toward income smoothing on listed manufacturing companies at the Indonesian Stock Exchange, 3) Winner/loser stock has positive influance toward income smoothing on listed manufacturing companies at the Indonesian Stock Exchange, 4) Debt to equity ratio has not positive influance toward income smoothing on listed manufacturing companies at the Indonesian Stock Exchange. Key words: Income smoothing, firm size, winner/loser stock, and debt to equity ratio